A population‐based, incidence cohort study of mid‐back pain after traffic collisions: Factors associated with global recovery. (17th February 2015) - Johansson, M.S.; Boyle, E.; Hartvigsen, J.; Jensen Stochkendahl, M.; Carroll, L.; Cassidy, J.D.
Abstract Background Traffic collisions often result in a wide range of symptoms included in the umbrella term whiplash‐associated disorders. Mid‐back pain (MBP) is one of these symptoms. The incidence and prognosis of different traffic injuries and their related conditions (e.g. neck pain, low back pain, depression or others) has been investigated previously; however, knowledge about traffic collision‐related MBP is lacking. The study objectives were to describe the incidence, course of recovery and prognosis of MBP after traffic collisions, in terms of global self‐reported recovery. Methods Longitudinal data from a population‐based inception cohort of all traffic injuries occurring in Saskatchewan, Canada, during a 2‐year period were used. Annual overall and age‐sex‐specific incidence rates were calculated, the course of recovery was described using the Kaplan–Meier technique, and associations between participant characteristics and time‐to‐self‐reported recovery were explored in 3496 MBP cases using Cox proportional hazards models. Results The yearly incidence rate was 236 per 100, 000 population during the study period, and was highest in women and in young persons. The median time‐to‐first reported recovery was 101 days (95% CI: 99–104) and about 23% were still not recovered after 1 year. Participant's expectation for recovery, general health, extent of severely affecting comorbidities and having experienced a previous traffic injury were some of the prognostic factors identified. Conclusions These findings show that MBP is common after traffic collisions, may result in a long recovery process and that a range of biopsychosocial factors are associated with recovery.